Ragazze pietrose (ad Ov. Met. II 708-835) - Silvia Romani (Annali Online dell'Università di Ferrara. Sezione Lettere)
Petrified Girl Aglauros is quite a complex figure in Greek and Roman mythology: she is the daughter of Kekrops, the very one who was given the basket containing the baby Erichthonios by Athene and she is the one, with her sisters, Pandrosos and Herses, who disobeyed the goddess and opened the casket of Erichthonios. She sacrificed herself by leaping from Acropolis in order to save the city during a war, as well. For that reason, the Athenians made a hieron for her on Acropolis. In Ovid’s Metamorphosis (II 278ss.), she turned into a stone when refuses to open the door and let the god Hermes in as a suitor of her sister, Herse. This paper aims at focusing on the pattern of petrification by reading Aglauros myth as a story case: the stoning of Aglauros in not only the story of a punishment, but also a symbolic account of a very peculiar way of metarmophosis, the transformation of a female body into a dead block: i.e. the physiological transmigration of blood, water, body fluids into the stone. Female body and statue occupy two adjacent universes that alternate seamlessly in the myths of ancient heroines so that female bodies of parthenoi, of heroines, apparently share a sort of petrified nature after death.